MENINGKATKAN PEREKONOMIAN UMKM FLANEL FLOWER DI MASA PANDEMI COVID MELALUI PROGRAM DIGITAL - Mu’azamsyah, Muhammad; Anisa, Anisa; Stiyanto, Handika; Lisa, Lisa; Saputra, Rengga; Astriyana, Yesti; Fatmawati, Yuli; Novemia, Dila; Sulaiman, Juanda; Zulfikar, Muhammd; Juita, Ria; Sosi, Sosi (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to educate and socialize MSME players about the use of e-commerce, WhatsApp business and the Seabank application in improving the economy of Flannel Flower MSMEs during the Covid 19 pandemic. Flannel Flower MSMEs are located on Jl. Mirror Hill, Simpang Gg. Diana No.1 Tanjungpinang and was established on August 18, 2016. Since its establishment, this business has not developed rapidly. This is because Flannel Flower MSMEs have several problems, such as not having a business license issued by the local sub-district (Bukit Cermin), never having attended training related to E-markets, product marketing is still around Tanjungpinang, using the Whatsapp application which is still a personal account, and all work is managed by yourself. Therefore, in order to help business owners develop their businesses, we run programs namely: a) outreach about e-commerce, Shopee, Seabank and WhatsApp business; b) e-commerce practices, namely creating a Flannel Flower UMKM shopee account and creating a seabank account; c) whatsapp business socialization and submission of business licenses; d) submission of to do list boards, evaluation of work programs, and distribution of souvenirs. The methods used in running the program include socialization, discussion and practice methods. The result of implementing this program is that the Flannel Flower UMKM has a business license from Bukit Cermin Village, has switched to using WhatsApp business and a Shopee account to carry out product sales transactions. However, the use of the Shopee account has not been maximized due to limited free shipping outside the Sumatra region and the difficulty of finding packing materials such as wooden packaging so that Flowel Flannel products do not experience any damage in the middle of the journey. Meanwhile, the use of the Seabank application cannot be realized because business owners are still hesitant to use online savings and are still comfortable using conventional banks.